The Lisbon Earthquake of November 1, 1755 - Martínez Solares, José Manuel (Física de la Tierra, 2017)
The 1755 earthquake of November 1, also called the Lisbon Earthquake for being the main city that suffered its multiple effects: earthquake, tsunami and fire. However, the affected area was very extensive, could be estimated at ten million square kilometres. The movement of the soil caused much damage in large parts of Spain, Portugal and Morocco, resulting in significant economic and social costs. The earthquake, with marine epicenter, also generated a noticeable alteration of the sea whose waves swept the Atlantic coasts of the Peninsula and North Africa. Also, as with large earthquakes (8,5 Mw, Martínez Solares, 2001), most of the hydrogeological effects that can be produce in nature, from cracks in the field to liquefaction, also occurred.